Demotivation and its relation with academic and psychosocial factors in university students - González Castro, Isolina (2021)
Introduction: School dropout represents a problem among higher education institutions, that prevails and affects the professional development of students. Objective: Prove relations between demotivation, teaching skills, satisfaction of academic expectations and tutoring in a University in a South of Sonora, México. Method: A scale of factors associated with dropping out was used (Tutoring Scale, Scale of Satisfaction of Academic Expectations, Scale of Teaching Competencies and Scale of Motivation), applied to 359 students from 6 different professions, chosen at random where 161 were men, 191 women, aged from 18 to 51 years old. Results: Tutoring, academic expectations satisfaction and teaching competences had a positive and significative covariances among these constructs. Regarding the demotivation factor, it was appreciated a negative covariance with the remaining constructs, which suggest the presence of divergent validity between this and the rest of the constructs. Conclusion: At higher levels of tutoring, academic and teaching competences expectations satisfaction, there will be lower levels of demotivation. The limitations of the study are discussed.